Design aesthetics as drivers of value in mobile banking: does customer happiness matter?. Issue 1 (18th July 2019) - Chaouali, Walid; Lunardo, Renaud; Ben Yahia, Imene; Cyr, Dianne; Triki, Abdelfattah
Abstract : Purpose: The purpose of this paper is to examine how customers derive value (functional, emotional, social and epistemic value) from the design aesthetics of mobile banking applications and then form intention to adopt mobile banking. Furthermore, this research investigates the moderating effect of happiness, which is predicted – and showed – to strengthen the effects of design aesthetics on value. Design/methodology/approach: A survey using screenshots of mobile banking applications was administered to a sample of 281 bank customers. Data were analysed using SmartPLS. Findings: The results show that design aesthetics have a positive effect on functional, emotional, social and epistemic value. In turn, these value dimensions positively affect intention to adopt mobile banking. The findings also demonstrate that happiness moderates the effects of design aesthetics on these value dimensions. Practical implications: This work can be useful to designers of banking applications and other practitioners to improve their policies and strategies related to mobile applications. Originality/value: This research represents an initial attempt to examine how customers derive functional, emotional, social and epistemic value from design aesthetics in mobile banking. In addition, this research demonstrates that happiness moderates – and more specifically strengthens – the effects of design aesthetics on customer value. The results provide a theoretical contribution to the importance of value in customer decision making, and in the current case, in the seldom-researched area of mobile banking.